2013
DOI: 10.1177/1084713813495459
|View full text |Cite
|
Sign up to set email alerts
|

How Linguistic Closure and Verbal Working Memory Relate to Speech Recognition in Noise—A Review

Abstract: The ability to recognize masked speech, commonly measured with a speech reception threshold (SRT) test, is associated with cognitive processing abilities. Two cognitive factors frequently assessed in speech recognition research are the capacity of working memory (WM), measured by means of a reading span (Rspan) or listening span (Lspan) test, and the ability to read masked text (linguistic closure), measured by the text reception threshold (TRT). The current article provides a review of recent hearing research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
160
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(178 citation statements)
references
References 81 publications
(224 reference statements)
13
160
3
2
Order By: Relevance
“…Recent work on memory for sentences heard in noise shows that memory performance correlates with WMC for individuals, both with normal hearing (Rönnberg, Rudner, Lunner & Stenfelt, 2014) and with hearing loss (Ng, Rudner, Lunner, Pedersen & Rönnberg, 2013). In two separate reviews, analyzing twenty studies (Akeroyd, 2008) and twenty-one studies (Besser et al, 2013), it was found that in most of the studies the speech recognition in noise was most reliably predicted by WMC as measured by the reading span test (Daneman & Carpenter, 1980;Rönnberg, Arlinger, Lyxell & Kinnefors, 1989). In the domain of hearing aids, it has been shown that WMC correlates with aided speech recognition in noise performance (Foo, Rudner, Rönnberg & Lunner, 2007;Gatehouse, Naylor & Elberling, 2003, 2006a, 2006bLunner, 2003, Lunner andSundewall-Thorén, 2007).…”
Section: Working Memorymentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work on memory for sentences heard in noise shows that memory performance correlates with WMC for individuals, both with normal hearing (Rönnberg, Rudner, Lunner & Stenfelt, 2014) and with hearing loss (Ng, Rudner, Lunner, Pedersen & Rönnberg, 2013). In two separate reviews, analyzing twenty studies (Akeroyd, 2008) and twenty-one studies (Besser et al, 2013), it was found that in most of the studies the speech recognition in noise was most reliably predicted by WMC as measured by the reading span test (Daneman & Carpenter, 1980;Rönnberg, Arlinger, Lyxell & Kinnefors, 1989). In the domain of hearing aids, it has been shown that WMC correlates with aided speech recognition in noise performance (Foo, Rudner, Rönnberg & Lunner, 2007;Gatehouse, Naylor & Elberling, 2003, 2006a, 2006bLunner, 2003, Lunner andSundewall-Thorén, 2007).…”
Section: Working Memorymentioning
confidence: 99%
“…Besser et al, 2013;Mattys, et al, 2012). Furthermore, aging is associated with hearing loss (Pichora-Fuller & Singh, 2006).…”
Section: Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes are called top-down processes, while the perception of sound and the ability to hear is rather referred to as bottom-up processes (Avivi-Reich, Daneman, & Schneider, 2014;Besser, Koelewijn, Zekveld, Kramer, & Festen, 2013;Davis & Johnsrude, 2007;Zekveld, Heslenfeld, Festen, & Schoonhoven, 2006). For example, the acoustic analysis and intensity coding of speech are, more or less, unconscious and automatic bottom-up processes, while linguistic processes and the use of internal speech representations to facilitate speech identification are top-down processes (Zekveld et al, 2006).…”
Section: Introductionmentioning
confidence: 99%